2015
DOI: 10.1007/s12257-014-0706-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous improvements in the activity and stability of Candida antarctica lipase B through multiple-site mutagenesis

Abstract: An enzyme with improved characteristics is required for biochemical processes to be economically feasible. In this study, improvements in both the stability and activity of Candida antarctica lipase B (CALB) were integrated through multiple-site mutagenesis. CALB was divided into two regions to optimize its performance. Modulating the flexibility within the substrate-binding region and the hydrophilic solvent-affecting region can enhance the catalytic activity and organic solvent stability of CALB, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The influence of CalB mutations in helices α5 and α10 on esterase and lipase activity toward short-chain and long-chain para-nitrophenyl (pNP) compounds is well established. Yagonita et al found that V139E and A151D mutations yielded a 5-fold increase in activity against pNP caprylate. Circular permutations that significantly altered the substrate recognition or adsorption interface of CalB yielded multiple variants with increased activity toward pNP butyrate and DiFMU octanoate .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The influence of CalB mutations in helices α5 and α10 on esterase and lipase activity toward short-chain and long-chain para-nitrophenyl (pNP) compounds is well established. Yagonita et al found that V139E and A151D mutations yielded a 5-fold increase in activity against pNP caprylate. Circular permutations that significantly altered the substrate recognition or adsorption interface of CalB yielded multiple variants with increased activity toward pNP butyrate and DiFMU octanoate .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Mutations which increased rigidity in the solvent affecting region (A92E and T245S) showed higher methanol stability, but were less catalytically active, than the variants with activity enhancing mutations (V139E and A151D) and vice versa. The combination of both mutations resulted in mutants (V139E, A92E and V139E, T245S) that were more active and stable in presence of methanol (Yagonia et al 2015).…”
Section: Residue Flexibilitymentioning
confidence: 99%
“…One approach to engineering enzymes is to introduce mutations at their active sites when the structures are available, in particular for the residues to interact with substrates (Yagonia et al, 2015;Lee et al, 2019). In addition, understanding the catalytic mechanism may provide useful insights into how a particular amino acid residue functions in enzymatic reactions.…”
Section: Engineering Of Coenzyme B 12 -Dependent Gdht Improvement In mentioning
confidence: 99%